Quizizz's Augmented Reality (AR) Based Mathematics Digital Pocketbook Design Using GOLD (Guided, Organizing, Leaflet, Discovery) Learning Model - Feri Tiona Pasaribu; Yelli Ramalisa (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research was conducted with the aim of meeting the needs of students in learning in the 21st century, where both students and educators are required to have good skills in utilizing technology in the learning process, especially when conducting distance education. This study aims to produce a digital pocket book based on Augmented Reality (AR) assisted by quizizz using the GOLD (Guided, Organizing, Leaflet, Discovery) learning model. This research is a development research that uses 4-D models (Four-D Models). Which consists of 4 stages of development, namely, the definition stage (define), the planning stage (Design), the development stage (develop), and the dissemination stage (Disseminate). The results of this study indicate that the product produces a useful pocket book. With a pocket book quality level based on 3 criteria, namely: valid and practical. From the research results obtained: 1) the percentage of pocket book validity from material experts 88% (very valid) and from design experts 87.6% (very valid), 2) the percentage of pocket book practicality by educators 88.75% (very practical) and by students 88, 8% (very practical). This research is still limited to testing the validity and practicality of digital pocket book.